7th International Energy Conversion Engineering Conference 2009
DOI: 10.2514/6.2009-4565
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency Nuclear Power Plants Using Liquid Fluoride Thorium Reactor Technology

Abstract: An overall system analysis approach is used to propose potential conceptual designs of advanced terrestrial nuclear power plants based on Oak Ridge National Laboratory (ORNL) Molten Salt Reactor (XISR) experience and utilizing Closed Cycle Gas Turbine (CCGT) thermal-to-electric energy conversion technology. In particular conceptual designs for an advanced 1 GWe power plant with turbine reheat and compressor intercooling at a 950 K turbine inlet temperature (TIT), as well as near term 100 1VIWe demonstration pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…3 Figure 1 shows that station thermodynamic states of such a helium gas turbine converter are well within the range demonstrated by the SSME except for the heater and first stage turbine inlet. The heater is conceptualized as being built of Hafnium Carbide tubes, heated uniformly by intense sunlight.…”
Section: Intense Efficient Conversion Architecture (Inca)mentioning
confidence: 87%
See 1 more Smart Citation
“…3 Figure 1 shows that station thermodynamic states of such a helium gas turbine converter are well within the range demonstrated by the SSME except for the heater and first stage turbine inlet. The heater is conceptualized as being built of Hafnium Carbide tubes, heated uniformly by intense sunlight.…”
Section: Intense Efficient Conversion Architecture (Inca)mentioning
confidence: 87%
“…Helium Brayton cycles are already used in the nuclear power industry, 2 with the intercooled helium Brayton cycle of the DOE (ORNL) liquid fluoride nuclear power plant cycle. 3 Here we adapt such cycles with the heat coming from solar radiation. Initial cycle analyses show that station thermodynamic states of such a helium gas turbine converter, are well within the range demonstrated by the Space Shuttle Main Engine.…”
Section: Introductionmentioning
confidence: 99%
“…The large change in the reactivity is caused by the higher burnup rate of Downloaded by [University of Regina] at 14:53 18 November 2014 Figure 15. The thermal efficiency of a gas turbine direct Brayton cycle in GT-MHR as a function of turbine inlet temperature [13]. 113 Cd, which results in the complete depletion of 113 Cd before the reactor reaches the target burnup.…”
Section: Loading Of Bp Particlesmentioning
confidence: 99%
“…Figure 15 shows the change of plant efficiency as a function of the turbine inlet temperature [13]. So far, regarding the effect of the turbine inlet temperature on the thermal efficiency of the GT-MHR, it has been reported that the increase or decrease of the outlet coolant temperature every 50 K, without changing the other parameters, resulted in the change of thermal cycle efficiency by approximately 1.75% [14].…”
Section: Estimation Of the Change In Thermal Efficiencymentioning
confidence: 99%
“…Heat exchangers are essential components in space heating, refrigeration, air conditioning, and chemical and petrochemical plants and refineries. They also have a major role in the implementation of various thermodynamic cycles in large electrical power plants and heat engines, including Closed Cycle Gas Turbines (CCGT) for stationary conventional fueled or nuclear power plants [1][2][3] or propulsion systems 4 where efficient conversion of thermal-to-electrical energy or rotary shaft work energy is a principal objective. For the variety of heat exchanger design configurations for each particular application, which may range from shell-tube to plate-fin designs in parallel flow, counterflow, or crossflow configurations, refer to the many texts in this field.…”
Section: Introductionmentioning
confidence: 99%